Dew drops on spider web appearance: a newly named pattern of IgG4 deposition in pemphigus with direct immunofluorescence - Dmochowski, Marian; Gornowicz-Porowska, Justyna; Bowszyc-Dmochowska, Monika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Novel appearances in cutaneous pathology as well as mucocutaneous clinical signs are being described which indicate that this is still an attractive area for exploration. The H + E histology terms of “decorated tomb stoning” and “undecorated tomb stoning”, advocated by some pathologists, are misleading and as such should be avoided. Here, an appearance of IgG4 pemphigus deposits examined cost-effectively with direct immunofluorescence and suggested to be called “dew drops on spider web” is depicted in depth.